WHATSAPP (WA) DAN KONSEP JARAK SOSIAL BARU DI MASYARAKAT - Afina Amna (President University, 2018)
Abstract. Whatsapp (WA) as a new social media changes people's communication in cyberspace. Communication that initially can only be done in the real world, develops with the existence of cyberspace that makes communication can be done without having to meet, and can be done quickly and can be felt as if real. For this reason, this study aims to find out how public communication is before there is WA and after there is WA? Does WA change the concept of social distance for society? This research is important to do so that we know how WA as an active and massive communication media used by the community can change the concept of new social distance in society. The method used is qualitative data collection through interviews with several WA users. This interview was conducted by random sampling method with the selection of informants randomly. The theory used in this study is the theory of social distance. This study found that WA changed communication in cyberspace and WA also changed the concept of new social distance because after massive WA groups were used, people were free to disseminate information and had the right to comment without fear of social distance in the real world. People can also more easily realize their sympathies because groups in WA make it easier for them to carry out information and coordination to be able to carry out activities that show sympathy for others.Keywords: Communication, Whatsapp, Social Distance